PENYIDIKAN TAMBAHAN DALAM PERKARA PIDANA - SATRIANA, I MADE WAHYU CHANDRA (Fakultas Hukum Universitas Dwijendra, 2016)
ABSTRACTÂ The obligation for investigators to conduct additional investigation, in case of the return of the case file from the prosecutor to the investigator because of the imperfection of the case file. In Article 138 (2) KUHAP has opened an opportunity for investigators to cooperate with a matching public prosecutor in an effort to complete the case file, which the investigator can consult the difficulties encountered. with a relatively short time can be used by investigators to be able to complete the investigation properly and can restore the complete case file in accordance with the instructions of the public prosecutor.